Perancangan Furniture “Knockdown” Berbasis Magnet untuk Apartemen Tipe Studio - Yoke Maldiputra; Stephanus P Honggowidjaja; Grace Setiati Kattu (Intra, 2018)
Apartments have several types of rooms, but the most commonly used is studio type. The average studio-type apartment has a narrow living space and no living room so guests who wish to visit eventually sit in bed or in less appropriate places. Therefore the need for furniture that can meet all the needs in one space. In this article the product is designed in the form of a set of furniture for the living room with a magnet base as its join. This furniture uses knockdown construction system so it can be dismantled and can be stored in flat pack. The concept taken for design this time is by combining natural materials with industrial materials, from here taken the theme of the concept, named